PEMBELAJARAN MEMBACA PERMULAAN DENGAN METODE FONIK DI TADIKA AL-FIKH ORCHARD AYER TAWAR, PERAK MALAYSIA - Pratiwi, Mila; Harfiani, Rizka (Yayasan Rahmat Islamiyah, 2024)
Reading is a basic human ability to obtain information by understanding the meaning contained in each piece of writing. Teachers have a very important role in designing the use of methods, media and strategies to stimulate students' reading abilities and achieve learning goals. This research aims to analyze the application of the phonics method in beginning reading learning to find out how to stimulate students' reading abilities at Tadika Al-Fikh Orchard Ayer Tawar Perak Malaysia. This research uses a qualitative method with a case study type of research and a field approach (Field Research), data collection techniques are carried out by means of observation, interviews and documentation. Meanwhile, data analysis is carried out through 4 stages, namely data collection, data condensation, data display, and drawing conclusions (verification). Early childhood children's ability to read is usually driven by environmental factors, be it family, teachers or appropriate learning systems. The steps for initial reading learning using the phonics method are: planning initial reading learning using the phonics method, implementing initial reading learning using the phonics method, and evaluating initial reading learning using the phonics method. Based on the research results, early reading learning using the phonics method is very good for developing students' language skills, especially in reading.